2010
DOI: 10.4141/cjps09175
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of long-term marketable yield of carrot and onion cultivars in muck (organic) soil in relation to seasonal weather

Abstract: Tesfaendrias, M. T., McDonald, M. R. and Warland, J. 2010. Consistency of long-term marketable yield of carrot and onion cultivars in muck (organic) soil in relation to seasonal weather. Can. J. Plant. Sci. 90: 755Á765. To identify carrot and onion cultivars that provide consistent marketable yields, we tracked the yields of five fresh market carrot [Daucus carota L. subsp. sativus (Hoffm.) Arcang.] and six onion (Allium cepa L.) cultivars for at least 13 yr. Relationships between longterm weather variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…In these plants, there was an increased sensitivity heat stress 7 to 15 days before anthesis, coincident with pollen development. Subjecting plants to a more intense heat stress (generally greater than 4°C above optimum) resulted in severe yield loss extending to complete crop failure (Ghosh et al, 2000;Sato et al, 2000;Kadir et al, 2006;Gote and Padghan, 2009;Tesfaendrias et al, 2010). Tomatoes under heat stress fail to produce viable pollen while their leaves remain active.…”
Section: Annual Cropsmentioning
confidence: 97%
See 1 more Smart Citation
“…In these plants, there was an increased sensitivity heat stress 7 to 15 days before anthesis, coincident with pollen development. Subjecting plants to a more intense heat stress (generally greater than 4°C above optimum) resulted in severe yield loss extending to complete crop failure (Ghosh et al, 2000;Sato et al, 2000;Kadir et al, 2006;Gote and Padghan, 2009;Tesfaendrias et al, 2010). Tomatoes under heat stress fail to produce viable pollen while their leaves remain active.…”
Section: Annual Cropsmentioning
confidence: 97%
“…When plants are subjected to mild heat stress (1°C to 4°C above optimal growth temperature), there was moderately reduced yield (Sato, 2006;Timlin et al, 2006;Wagstaffe and Battey, 2006;Tesfaendrias et al, 2010). In these plants, there was an increased sensitivity heat stress 7 to 15 days before anthesis, coincident with pollen development.…”
Section: Annual Cropsmentioning
confidence: 97%
“…The marketable yield of most of the cultivars in this trial was within the 8.4-26 t ha −1 range recorded in 15 commercial carrot cultivars by Brandenberger et al (2007). In contrast, Tesfaendrias et al (2010) evaluated 24 cultivars for many years and found significant environment by cultivar interaction and recorded marketable yields of 78-95 t ha −1 from the top six cultivars. The maximum marketable yields of Nantes and DZARC-5 recorded in Experiments 1 and 3 were 26-55 t ha −1 lower than the results of Tesfaendrias and coinvestigators, which might be due to differences in cultivar, soil and level of management.…”
Section: Experiments 3: Evaluation Of Selected Carrot Cultivars For Yimentioning
confidence: 62%
“…When plants are subjected to mild heat stress (1-4 C above optimal growth temperature), there was moderately reduced yield [38][39][40][41]. In these plants, there was an increased sensitivity to heat stress 7-15 days before anthesis, coincident with pollen development.…”
Section: Crop Responses To Climate Changementioning
confidence: 99%
“…In these plants, there was an increased sensitivity to heat stress 7-15 days before anthesis, coincident with pollen development. Subjecting plants to a more intense heat stress (generally greater than 4 C increase over optimum) often resulted in severe yield loss up to and including complete failure of marketable produce [33,[41][42][43][44]. There is evidence that temperature effects on yield loss vary among crops and among cultivars within crops.…”
Section: Crop Responses To Climate Changementioning
confidence: 99%